Ineffectiveness of the Issuance of Investigation Orders After Examining the Reporter in the Investigation Process at the Indonesian National Police - Hendra Gunawan; Ahmad Redi (Riviera Publishing, 2024)
This study examines the ineffectiveness of issuing Investigation Orders (Surat Perintah Penyidikan or Sprindik) following complainant examinations in Indonesia’s law enforcement process, contributing to case backlogs. Using a normative juridical method, the research analyzes legal regulations, administrative procedures, and relevant case examples. A statutory approach involving legal reviews and a conceptual approach exploring legal accountability and procedural justice principles were applied. Key findings reveal that high investigator workloads, inadequate training, and administrative mismanagement hinder effective Sprindik issuance. A lack of standardized protocols for evaluating initial evidence leads to premature suspect designations, causing judicial delays. Limited use of investigative technologies and procedural misunderstandings further exacerbate inefficiencies. To address these issues, the study recommends revising police regulations to standardize evidence evaluation, expanding investigator training, streamlining administrative processes, and adopting digital case management systems. An oversight mechanism should be established to monitor Sprindik issuance, ensuring greater accountability and transparency. These reforms aim to modernize investigative procedures, reduce case backlogs, and promote fairer, more efficient law enforcement practices. The study’s integrated approach combines legal analysis with policy solutions, offering a roadmap for sustainable improvements in criminal investigation management.